Evaluation of Non Isolated DC-DC Boost Converter for Interfacing Solar Pv Panel - Abubakar, Hafs Musa; Abdullahi, Bako; Auwal, Mustapha Imam; Muhammad, Naziru yahaya; Huzaifa, Isah (Journal of Energy Conservation, 2024)
Many renewable energy sources such as solar and wind energy are grown and well developed as the cost effective solution being widely used in Nigeria but the whole Africa and world at large has witnessed a dramatic increase, concern over environment and demand of energy have led the world to think about alternate energy sources such as wind, hydro, solar and fuel cells. The voltage multiplier cell was incorporated with the interleaved converter to design the DC to DC boost converter for the PV application. The proposed converter is supplied by 18V as an input voltage and produces 99V output and gives 95% of efficiency under no load and 94% under load conditions. The performance of the proposed topology was substantiated and the results achieved from the fabricated prototype are in good agreement with the design strategies. The effects of input parameters such as sun radiation and useful power input on PV system and DC-DC converter outputs were exploration for 14 days. Results confirmed that the DC-DC converter was perfectly designed and accurately constructed, when integrated with solar PV system, data were captured under no load and on load conditions.
Keywords: DC-DC converter; Photovoltaic (PV); interleaved switch; High gain; Duty-cycle; solar irradiance; useful solar power input